2012
DOI: 10.1177/1753425912462752
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic stress and pro-inflammatory cytokine responses to an intravenous corticotropin-releasing hormone challenge of Brahman cattle following transportation

Abstract: This study was designed to characterize potential sexually dimorphic stress and immunological responses following a corticotropin-releasing hormone (CRH) challenge in beef cattle. Six female (heifers) and six male (bulls) Brahman calves (264 ± 12 d of age) were administered CRH intravenously (0.5 µg of CRH/kg body mass) after which serum concentrations of cortisol increased from 0.5 h to 4 h. From 1 h to 4 h after CRH administration, serum cortisol concentrations were greater in heifers than in bulls. In all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…In the present study, PNS females had greater EV through weaning than control females, PNS males, or control males. Other investigators have reported female cattle to be more temperamental (Shrode and Hammack, 1971;Hoppe et al, 2010), with heifers having greater blood concentrations of cortisol compared with bulls (Lay et al, 1992;Hulbert et al, 2012) and steers having greater cortisol compared with bulls (Tennessen et al, 1984). In the present study, female calves had greater serum concentrations of cortisol relative to males.…”
Section: Factors Affecting Temperament and Adrenocortical Function Insupporting
confidence: 54%
“…In the present study, PNS females had greater EV through weaning than control females, PNS males, or control males. Other investigators have reported female cattle to be more temperamental (Shrode and Hammack, 1971;Hoppe et al, 2010), with heifers having greater blood concentrations of cortisol compared with bulls (Lay et al, 1992;Hulbert et al, 2012) and steers having greater cortisol compared with bulls (Tennessen et al, 1984). In the present study, female calves had greater serum concentrations of cortisol relative to males.…”
Section: Factors Affecting Temperament and Adrenocortical Function Insupporting
confidence: 54%
“…This is in agree ment with a study utilizing a cimaterol treatment in steers, where no difference in cortisol concentrations were ob served 1 and 13 d following initiation of oral dosing (Chikhou et al, 1991). The temporal pattern associated with an acute increase in circulating concentrations of cor tisol followed by a subsequent decline in the current study is similar to that observed in Brahman calves in response to a CRH challenge (Hulbert et al, 2013), although the magnitude of the cortisol response was greater in the cur rent study. Control heifers produced a greater cortisol response to the CRH/VP challenge compared with ZIL heifers, thus suggesting a possible downregulation of as pects associated with HPA axis regulation.…”
Section: Discussionsupporting
confidence: 89%
“…Although VT remained increased in CON heif ers, a return to baseline and subbaseline values was ob served in ZIL heifers. The temporal VT response to the CRH/VP challenge in the current study has similarities to the response observed in weaned Brahman calves chal lenged with CRH; in that study the authors reported fluc tuations in rectal temperature in the 8h period following CRH administration (Hulbert et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…In comparison, administration of 0.5 mg of bCRF/kg BW intravenous to Brahman calves enhanced serum cortisol concentrations with a peak value at 30 min (approximately 110 nmol/L in heifers (n ¼ 6) compared with 70 nmol/L in bulls (n ¼ 6)) [102]. After administration of 0.03 mg bCRF/kg BW intravenous in Holstein-Friesian heifer calves (n ¼ 20), the plasma cortisol concentration was approximately 28 to 61 nmol/L within about 30 min and the plasma ACTH concentration was approximately 3.3 to 7.7 pmol/L within about 15 min [103].…”
Section: Corticotropin-releasing Factor Challenge Testmentioning
confidence: 94%